1985
DOI: 10.1037/0012-1649.21.4.666
|View full text |Cite
|
Sign up to set email alerts
|

Physical maturation rate and cognitive performance in early adolescence: A longitudinal examination.

Abstract: A longitudinal study was undertaken to examine (a) the development of the relationship between physical maturation rate and cognitive performance as children become adolescent and (b) the specific components of cognitive processing that are most closely linked to physical maturation rate. Seventy-eight girls and 67 boys were examined prepubertally on a battery of cognitive ability and perceptual asymmetry measures and reexamined 2 years later when secondary sex characteristics could be evaluated as a measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 47 publications
1
21
1
2
Order By: Relevance
“…These results directly contrast with those reported by Waber (1976). Most recently, Waber et al (1985) conducted a longitudinal study to assess 78 girls and 67 boys both before puberty and 2 years later. At the later time, children who could be classified into extreme groups of early and late maturers were reassessed on a battery of cognitive measures and a dichotic CV discrimination task.…”
contrasting
confidence: 78%
See 2 more Smart Citations
“…These results directly contrast with those reported by Waber (1976). Most recently, Waber et al (1985) conducted a longitudinal study to assess 78 girls and 67 boys both before puberty and 2 years later. At the later time, children who could be classified into extreme groups of early and late maturers were reassessed on a battery of cognitive measures and a dichotic CV discrimination task.…”
contrasting
confidence: 78%
“…However, Waber's suggestion that hemispheric lateralization may be the mechanism accounting for this effect has not been replicated by the few investigators that have attempted to do so (Meyer-Bahlburg et al, 1985;Rovet, 1983;Waber et al, 1985). For example, Meyer-Bahlburg et al (1985) administered monotic word discrimination and dichotic consonantvowel syllable (CV) discrimination listening tests to 12 idiopathic precocious puberty (IPP) adult females and their matched controls.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…There is no clear association between puberty and cognitive processes. Some studies have found a link between spatial abilities and pubertal timing (Petersen, 1976; Waber, Mann, Merola, & Moylan, 1985), but others have not (Orr, Brack, & Ingersoll, 1988; Strauss & Kinsbourne, 1981). Puberty may influence the degree to which one can exert cognitive control in situations of high arousal but in itself may not be directly linked to the development of cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…Later maturation, independent of gender, was found to be associated with better performance on spatial ability measures; however, age of sexual maturation was not related to performance on measures of language-related ability. Several subsequent studies have replicated, or partially replicated, this relationship between age of pubertal onset and spatial ability in samples of adolescents (Diamond, Carey, & Back, 1983;Newcombe & Bandura, 1983;Waber, Bauermeister, Cohen, Ferber, & Wolff, 1981), while other studies have failed to find such a relationship (Petersen, 1976;Waber, Mann, Merola, & Moylan, 1985).…”
mentioning
confidence: 85%